Language Register in The Silence - Chutintaranond, Thanasin (Journal of Fine and Applied Arts Khon Kaen University, 2024)
This qualitative research employed textual analysis and in-depth interview methods along with data triangulation. The aim of this study was to analyse the language register in a film, The Silence (2019). The results revealed that the language register in this film could divided into 3 registers which were 1) sound register 2) crisis register and 3) religion register. All registers were useful in order to make characters and situations realistically, create unity and imitate code choices in human communication. Moreover, The silence was confirmed that environment and communication conditions are significant factors in terms of code choices for human beings.